Evaluating Electrochemical Marker for Udavarta (Slow Transit Constipation) and Risk of Cardiovascular Events: A Cross-Sectional Study - Divya Kajaria; Punam N. Khobarkar (Indian Journal of Community Medicine)
The known risk factors for cardiovascular diseases (CVDs) are diabetes, obesity, unhealthy diet, lack of exercise, smoking, and excessive use of alcohol. The 10-year cardiovascular risk factor prevalence of hypertension, obesity, and diabetes mellitus is 55.8%, 14.4%, and 9.8%, respectively. Besides these known risk factors, other potential but less searched risk factors also need to be explored for better prevention of CVDs. To evaluate the association between Udavarta (STC), changes in lead III of ECG, and heart disease score to demonstrate the earliest pathological changes in the heart. A cross-sectional observational study using a survey method to collect data from November 11, 2021 to January 5, 2022. The Udavarta symptom score (USS) is associated with ECG changes in lead III (P > 0.0098). The USS shows an association with the Hrudroga (heart disease) symptom score: relative risk 1.83 (95% CI: 1.20–3.1), odds ratio 5.65 (95% CI: 1.06–30), and P > 0.0385. Udavarta (slow transit constipation) shows a strong association with heart disease symptom score and lead III ECG changes, and clinically is an equally contributing risk factor for the development of CVDs compared to the other risk factors. This study reports that the minimum duration of constipation for starting the development of heart diseases assessed by ECG is 3 months, and the maximum duration is 25 years. This study emphasizes that slow transit constipation is a risk factor for developing heart disease. Clinical research in this direction is warranted.